2022
DOI: 10.1002/aqc.3781
|View full text |Cite
|
Sign up to set email alerts
|

Computing ship strikes and near miss events of fin whales along the main ferry routes in the Pelagos Sanctuary and adjacent west area, in summer

Abstract: The Mediterranean Sea is a high‐density maritime traffic area, particularly in the Pelagos Sanctuary. Ship strikes pose a substantial threat to fin whales (Balaenoptera physalus) according to reports from the IUCN, the IWC, the ACCOBAMS and the EU Habitats Directive. Near miss events (NMEs) were collected, as a proxy indicator of ship strikes for fin whales, along the main ferry routes crossing the Pelagos Sanctuary and adjacent western waters during ‘summertime’ (April to October). The ‘Fixed Line Transect Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The majority of recorded breaches instead occurred at a large distance from the ferry, which was not influenced by the observation conditions (i.e., sea state). The surveyed route is considered an area with a medium level of near miss events (David et al, 2022) and previous findings indicated a general low intensity of traffic and less vessels in the presence of fin whale sightings with respect to the number of ships observed in locations randomly sampled (Campana et al, 2015(Campana et al, , 2017; in this study, breaching events also occurred in areas with low maritime traffic. However, maritime traffic, particularly large ships, characterizing the western Mediterranean Sea represents a strong pressure on the marine environment.…”
Section: Environmental Social Anthropogenic Factorsmentioning
confidence: 68%
See 1 more Smart Citation
“…The majority of recorded breaches instead occurred at a large distance from the ferry, which was not influenced by the observation conditions (i.e., sea state). The surveyed route is considered an area with a medium level of near miss events (David et al, 2022) and previous findings indicated a general low intensity of traffic and less vessels in the presence of fin whale sightings with respect to the number of ships observed in locations randomly sampled (Campana et al, 2015(Campana et al, , 2017; in this study, breaching events also occurred in areas with low maritime traffic. However, maritime traffic, particularly large ships, characterizing the western Mediterranean Sea represents a strong pressure on the marine environment.…”
Section: Environmental Social Anthropogenic Factorsmentioning
confidence: 68%
“…Despite the current conservation measures applied, many anthropogenic activities affect cetacean species in the Mediterranean Sea (Coll et al, 2012; UNEP‐MAP, 2010). Maritime traffic represents one of the major threats to fin whales, which appear highly vulnerable to collisions (David et al, 2022; Ham et al, 2021; Laist et al, 2001). In the area under study, the presence of large ports and tourist destinations determine higher maritime traffic in the Tyrrhenian Sea than in the Sardinian‐Balearic basin, with a general increase during spring and summer in both basins (Campana et al, 2015, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Using multispecies occupancy models to map potential hotspots of depredation may help to reduce the deployment of acoustic deterrents and minimize the associated negative impacts (Estabrook et al 2016, Snape et al 2018). Similarly, fin whales Balaenoptera physalus and sperm whales Physeter macrocephalus are at high risk of collision with ferries in the northwestern Mediterranean Sea and in particular in the Pelagos sanctuary marine protected area (Ham et al 2021, David et al 2022). Mapping collision risk with multispecies occupancy models can ultimately direct the measures of speed limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The fin whale is the second most commonly observed species after the striped dolphin, and migrates to the north‐western part for feeding during summer, whilst the vessel traffic is high (Notarbartolo‐di‐Sciara et al, 2003; Panigada et al, 2006). Collisions with large vessels present a major conservation issue for the fin whale because they represent the primary fatal threat (David et al, 2022; Pace et al, 2015). The number of stranded fin whales from 1990 to 2009 was constant over time with an average of 2.5 individuals per year (Dhermain et al, 2015).…”
Section: Discussionmentioning
confidence: 99%